Analysis of Accountability and Transparency in Management of School Operational Assistance (BOS) on School Progress at SMP Muhammadiyah 16 Lubuk Pakam - Nashuha Harahap, Vania Ananda; Nurwani, Nurwani; Nasution, Juliana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
SMP Muhammadiyah 16 Lubuk Pakam is a private school that facilitates underprivileged children and also provides assistance in the form of School Operational Assistance (BOS) funds from the government. The purpose of this study was to analyze accountability and transparency in the management of school operational assistance funds for the progress of SMP Muhammadiyah 16 Lubuk Pakam. This study uses descriptive qualitative methods and data collection techniques by means of observation, interviews, and documentation. BOS Funding is based on the total number of students totaling 135 students. The results of the study show that the application of the principle of transparency at SMP Muhammadiyah 16 Lubuk Pakam is less transparent as seen from the lack of openness in planning the RKAS, the use of BOS funds, and the publication of reports on the use of BOS funds which are reported annually to parents and teachers because there is data that is private. The application of the principles of accountability and transparency at SMP Muhammadiyah 16 Lubuk Pakam can be seen in the form of accountability to all parties involved. Starting from the planning of BOS funds, the use of BOS funds that are in accordance with those determined by the central government, the accountability of BOS funds that are reported to internal and external parties, and the archiving of BOS funds documents that are archived by the BOS treasurer.